Pengaruh Konten Media Sosial dan Kualitas Informasi pada Fenomena #Presiden3periode Terhadap Persepsi Masyarakat Generasi-Z di TikTok - Wulan Dary; Pipit Fitiyah (MUKASI: Jurnal Ilmu Komunikasi, 2023)
This study aims to determine whether there is an influence of social media content and information quality on the #presidential3period phenomenon on the perception of Generation Z on TikTok. Reporting on the issue of President Jokowi for the 3rd period is currently a trending topic on social media and involves Generation Z who take part in a live demonstration on #presidential3period content on TikTok. This study uses the theory of diffusion of innovation (Everret M. Rogers, 1962) and uses and effects (Sven Windahl, 1979) with the assumption that the adoption of tiktok in generation Z has an effect in increasing understanding related to political content. This research uses quantitative research with positivism paradigm and expansive research nature. This study uses a questionnaire on generation Z with a range of ages 13-27 years, as the main method in obtaining data through Google Form. Respondents in this study were. The results in this study indicate that the variables X1 (Social Media Content) and X2 (Quality of Information significantly affect Public Perception (Y) is influenced by other variables that are not used by this study. This shows generation Z. can adopt TikTok media to access political information, especially on the issue of #president3period which causes an understanding effect on generation Z.